Replica exchange molecular dynamics of the thermodynamics of fibril growth of Alzheimer's Aβ(42) peptide - Han, Ming (American Institute of Physics, 2011)
The growth of amyloid fibrils is studied by replica exchange molecular dynamics in an implicit solvent. Our data indicate that extremely long simulation times (at least a few hundred ns) are necessary to study the thermodynamics of fibril elongation in detail. However some aspects of the aggregation process are already accessible on the time scales available in the present study. A peak in the specific heat indicates a docking temperature of T(dock) ≈ 320 K. Irreversible locking requires lower temperatures with the locking temperature estimated as T(lock) ≈ 280 K. In our simulation the fibril grows from both sides with the C-terminal of the incoming monomer attaching to the C-terminal of the peptides in the fibril forming a β-sheet on the fibril edge. Our simulation indicates that the C-terminal is crucial for aggregation.